Peculiarities and problems of eponyms (on the material of Kazakhstani periodicals) - Taubayev, Zharas; Rivers, William; Mussabekova, Ulzhan; Alimbayeva, Adiliya (Opción, 2019)
The purpose of this research paper is to collect eponyms from Kazakhstani political periodicals 2011 –2017 years. We used distance method which means to read, analyze and collect eponyms as units of investigation. Moreover, we used quantitative method in order to count eponyms. The authors arrive at a conclusion that given several peculiarities make eponyms unique and eponyms must be written with capital letters because of anthroponyms, but if the word goes through metonymical process the new eponym must be written with small letters. They recommend to use them frequently in the future in daily conversation and scientific life.